A Modified Monomeric Red Fluorescent Protein Reporter for Assessing CRISPR Activity - Højland Knudsen, Camilla; Ásgrímsdóttir, Emilía S.; Rahimi, Karim; Gill, Katherine P.; Frandsen, Søs; Hvolbøl Buchholdt, Susanne; Chen, Muwan; Kjems, Jørgen; Febbraro, Fabia; Denham, Mark (Frontiers in Cell and Developmental Biology, 2018)
Gene editing in human embryonic stem cells (hESCs) has been significantly enhanced by the discovery and development of CRISPR Cas9, a programmable nuclease system that can introduce targeted double-stranded breaks. The system relies on the optimal selection of a sgRNA sequence with low off-targets and high efficiency. We designed an improved monomeric red fluorescent protein reporter, GEmCherry2, for assessing CRISPR Cas9 activity and for optimizing sgRNA. By incorporating an out-of-frame sequence to the N-terminal of the red fluorescent protein mCherry, we created a visual tool for assessing the indel frequency after cutting with CRISPR Cas9. When a sgRNA-Cas9 construct is co-transfected with a corresponding GEmCherry2 construct, single nucleotide indels can move the GEmCherry2 sequence back in-frame and allow quantification and comparison of the efficiency of different sgRNA target sites by measuring red fluorescence. With this GEmCherry2 assay, we compared four target sites in the safe harbor AAVS1 locus and found significant differences in target site activity. We verified the activity using TIDE, which ranked our target sites in a similar order as the GEmCherry2 system. We also identified an AAV short inverted terminal repeat sequence within the Cas9 construct that, upon removal significantly improved transient transfection and expression in hESCs. Moreover, using GEmCherry2, we designed a sgRNA to target SORCS2 in hESCs and successfully introduced indels into the coding sequence of SORCS2.